The Rivalry of Football Supporters in Indonesia at Fanaticism Frame of Bonek and Aremania - Abd. Bassith Tamami; Nasution Nasution; Wisnu Wisnu (Journal Research of Social Science, Economics, and Management, 2021)
The presence of football supporters is very meaningful and is a very important element in a soccer match. However, in the football euphoria, there is a conflict between the supporters, one of the rivalries between supporters that is most often highlighted by the mass media is Bonek and aremania. This research was conducted to find out the root causes of supporters' rivalry between Bonek and aremania by using Johan Galtung's conflict theory. This research method is qualitative, the technique of determining the informants is purposive sampling. The data collection used in-depth interview techniques and document analysis. The results of this study in Johan Galtung's Conflict Theory, the existence of puppet problems with aremania can be categorized into three dimensions. The attitude dimension in puppet perception is related to aremania which is dominated by negative perceptions, as well as aremania perceptions of dolls. The dimensions of bonek behavior towards aremania tend to show a sense of competition and hostility that leads to violence, as well as aremania behavior towards dolls. The contradiction dimension of the puppet conflict with aremania is the creation of a heated situation with a high potential for clash or chaos.